Implementasi Kebijakan Pencegahan Penyalahgunaan Narkoba di Kabupaten Pesisir Selatan - Putri, Popy Mullya; Yusran, Rahmadani (Journal of Civic Education, 2025)
This study analyzes drug abuse prevention policies in South Pesisir Regency, applying Edward III’s Policy Implementation Model. The research used a descriptive qualitative method, gathering data through interviews, observation, and documentation. Findings show that implementation faces significant hurdles across four key areas; Communication: Policy information is not consistently distributed and lacks a unified message. Resources: Budget and personnel for implementation are limited. Disposition: While individual implementers are committed, they lack institutional support and proper incentives. Bureaucratic Structure: The system is not integrated into a permanent, cross-sectoral governance framework. However, the "Kampung Bebas Narkoba" (Drug-Free Village) program offers a promising bottom-up approach. It empowers communities and demonstrates the potential for multi-stakeholder collaboration to overcome formal bureaucratic limitations. The study concludes that successful drug prevention depends on a combination of national policy, strong local implementation, and active community participation.